2008
DOI: 10.1093/ndt/gfn419
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between silent brain infarction and chronic kidney disease

Abstract: Background. The presence of silent brain infarction (SBI) increases the risk of symptomatic stroke and dementia. The association between SBI and chronic kidney disease (CKD) has not been clarified. Moreover, little is known about what factors are related to SBI in CKD patients and whether the prevalence of SBI differs in CKD stage or cause of CKD.Methods. This is a cross-sectional study. A total of 375 subjects—335 with CKD and 40 with essential hypertension—were included. All subjects underwent magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 38 publications
2
68
0
2
Order By: Relevance
“…Many studies have found that CKD independently contributed to subclinical brain lesions on MRI, such as silent brain infarcts, lacunes, white matter hyperintensities, or cerebral microbleeds 10,11,[31][32][33][34][35] . These were mainly lesions of cerebral small vessel disease and could lead to brain atrophy and cortical thinning 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that CKD independently contributed to subclinical brain lesions on MRI, such as silent brain infarcts, lacunes, white matter hyperintensities, or cerebral microbleeds 10,11,[31][32][33][34][35] . These were mainly lesions of cerebral small vessel disease and could lead to brain atrophy and cortical thinning 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the hemodynamic stress to these vascular beds could result in small-vessel injuries to both brain and kidney. 15 Migraine was also associated with SBI. Among the patients with migraine with aura (MA), 8.1% of 161 subjects showed silent lesions.…”
Section: Epidemiology Of Sbi In Patients With Comorbiditymentioning
confidence: 97%
“…15 In another study, 25% of patients with a creatinine clearance (CCr) . 40 mL/min/1.73 m 2 showed SBI, 85% with a CCr , 40 mL/min/1.73 m essential hypertension (HTN) and normal renal function.…”
Section: Epidemiology Of Sbi In Patients With Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension plays an important role in the occurrence of silent brain infarction (a small vessel disease of the brain). This fact is more prominent in patients with CKD and is indicative of a cerebro-renal association, thus establishing a link between vascular disease of the kidney and the brain [31].…”
Section: Risk Factors For Cerebrovascular Remodellingmentioning
confidence: 97%